Sugarcane genetics: Underlying theory and practical application - Hengbo Wang; Yong-Bao Pan; Mingxing Wu; Junhong Liu; Shiwei Yang; Qibin Wu; Youxiong Que (Crop Journal)
Sugarcane is recognized as the fifth largest crop globally, supplying 80% of sugar and 40% of bioenergy production. However, sugarcane genetic research has significantly lagged behind other crops due to its complex genetic background, high ploidy (8–13×), aneuploidy, limited flowering, and a long growth cycle (more than one year). Cross breeding began in 1887 following the discovery that sugarcane seeds could germinate. Both self- and cross-pollination and selection were conducted by sugarcane breeders, but new cultivars were often eliminated due to disease susceptibility. Within the Saccharum genus, different species possess variable numbers of chromosomes. Wild sugarcane species intercrossed with each other, leading to development of the ‘Nobilization’ breeding strategy, which significantly improved yield, sucrose, fiber content, and disease resistance, and accelerated genetic improvement of cultivars. In recent years, scientific achievements have also been made in sugarcane genome sequencing, molecular marker development, genetic linkage map construction, localization of quantitative trait locus (QTL), and trait-associated gene identification. This review focuses on the progress in sugarcane genetic research, analyzes the technical difficulties faced, presents opportunities and challenges, and provides guidance and references for future sugarcane genetics research and cultivar breeding. Finally, it offers directions for future on sugarcane genetics.